Prevalência dos complexos microbiológicos verde e laranja em indivíduos com doença renal crônica em hemodiálise: revisão sistemática e metanálise - Manica, Jayne de Oliveira (2021)
Objective: To verify the prevalence of green and orange microbiological complexes in periodontal pockets of patients with chronic kidney disease (CKD) on hemodialysis. Materials and methods: This systematic literature review was conducted in accordance with the PRISMA statement. 12 databases were searched until February 2021. studies were selected blindly by two reviewers based on criteria of predefined eligibility. The risk of bias and the quality of evidence were assessed at from the NIH Quality Assessment Tool for Observational Cohort and Cross-sectional Studies. In addition, a quantitative analysis through meta-analysis of proportion was performed. Results: Of 4,737 articles found in all databases data, after applying the inclusion and exclusion criteria, 6 articles were selected initially by its title and abstract. After reading the selected articles in full, 1 article was excluded for not meeting the inclusion criteria and 5 were included. two There was a prevalence of Aggregatibacter actinomycetemcomitans (6.69%) belonging to the green complex and Prevotella intermedia (16.85%), Prevotella nigrescens (37.51%), belonging to the orange complex in periodontal pockets of patients with CKD on hemodialysis. Conclusion: In the subgingival microbiota of patients with CKD in hemodialysis, the bacterial complexes studied showed low prevalence. You studies on this subject are still scarce, requiring further studies to better understand the microbiological profile of patients and correlate it with the possible clinical and repair conditions for the control of this pathology.